Evaluation of Levonorgestrel Subdermal Implant as Long Term Reversible Contraceptive - Taqdees Iftikhar; Jehan Ara; Humaira Arshad; Nadra Sultana (Journal of Rawalpindi Medical College, 2018)
Background: To study the reasons of acceptability, efficacy,short term and long term side effects of Levonorgestrel Subdermal implant as long term reversible contraceptive. Methods: In this descriptive study women (n=13)were counselled regarding Levonorgestrel SDI. Levonorgestrel SDI was inserted sub-dermally in the upper arm under local anaesthesia. Information was collected regarding study specific variables. Follow up was performed at 1 and 6 months and 12,24 and 36 months. Results: Maximum number of patients wanting levonorgestrel subdermal implants were between 30-35 years. Majority of women opting for this procedure had 3-4 live issues. Majority (44%) of the women choose this method based on personal information. Most common side effect was heavy and irregular vaginal bleeding 18.7% after 6 months, and 17.3% after 12 months. Patients advised medical treatment for heavy menstrual bleeding did not respond well(cyclical progestogens and tranexamic acid). Fifteen percent of users got SDI removed by end of 12 months, mainly due to above side effects. The 3- year cumulative pregnancy rate was zero. Conclusion: Levonorgestrel SDI can be an acceptable, convenient and effective long term reversible contraceptive method. Menstrual disturbances and feeling of weight gain are the major reported side effects, leading to discontinuation of the method.